Unraveling the degradation mechanism for the hydrogen storage property of Fe nanocatalyst-modified MgH2. Issue 15 (23rd June 2022) - Song, Mengchen; Zhang, Liuting; Yao, Zhendong; Zheng, Jiaguang; Shang, Danhong; Chen, Lixin; Li, Hong
Abstract : Grain growth in MgH2 and Fe nanocatalysts during cycling was directly responsible for capacity loss and kinetic degradation. Abstract : Maintaining fast hydrogen storage kinetics is a key challenge for the practical application of MgH2 . To address this challenge, understanding the mechanism of kinetics that declines during cycling is crucial but it has not been systematically investigated to date. In this paper, three different Fe nanocatalysts were synthesized and then doped into MgH2 to form new composites. The MgH2 -Fe composite had significantly reduced operating temperatures and activation energy compared to that of undoped MgH2 . During cycling, a capacity retention of 93.4% was obtained after the 20 th cycle. For a better understanding of the declining performance, prolonged incubation was intentionally performed. Grain growth was found in MgH2 and the Fe nanocatalysts, which was directly responsible for capacity loss and kinetic degradation. These findings provide fundamental insights to facilitate designing and preparing catalytic hydrogen storage systems with superior cycling performance.